(untitled) (Research, Society and Development, 2020)
Visitors to urban natural areas can cause negative impacts on organisms and the environment. Considering the importance of urban parks for biodiversity conservation and the maintenance of environmental services, we characterized the profile of the visitors, the activities performed by them, and their negative impacts in the Chico Mendes Municipal Natural Park, Rio de Janeiro, Brazil. In 2018, we conducted interviews with 100 visitors and 3 park employees to obtain the visitors’ profile and the activities developed by them. Most visitors came from the surroundings (59%), had incomplete university degree or higher educational level (52%), and used to visit the park mostly on weekends and holidays (80%). Half of the visitors were between 31 and 50 years old and most of them were women (69%). The main motivation for the visits was to have contact with nature (68%). The harmful/forbidden activities most frequently reported were the use of unofficial trails, presence of exotic animals within the park, solid waste improperly disposed of in the park, feeding of local fauna, and unauthorized collection of plants. Visitors with a high level of education performed harmful/prohibited activities less frequently than the remaining ones (P = 0.0021). We recommend environmental education actions that emphasize the importance of respecting the park’s rules and that focus particularly on visitors with lower educational levels. The characterization of the visitors’ profile and the monitoring of their negative impacts over time must be part of an adaptive management plan for the park.